2012
DOI: 10.1111/j.1743-498x.2012.00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Introducing medical students to prehospital care

Abstract: The PCP is a successful and immensely popular addition to the MBBS curriculum at Barts and the London School of Medicine and Dentistry. We hope to observe and continue to support similar replications at other medical schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…This module commenced in 2008 as a response to increasing requests by Sheffield medical students for training in mountain rescue casualty care. This was in keeping with an increased interest in undergraduate teaching of prehospital emergency care [7][8][9][10][11][12][13]. Despite demand from students from surrounding areas, only 8 students were taken per year.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This module commenced in 2008 as a response to increasing requests by Sheffield medical students for training in mountain rescue casualty care. This was in keeping with an increased interest in undergraduate teaching of prehospital emergency care [7][8][9][10][11][12][13]. Despite demand from students from surrounding areas, only 8 students were taken per year.…”
Section: Discussionmentioning
confidence: 87%
“…Therefore team members must also be competent mountaineers. Lack of formal training in prehospital care leaves medical students ill prepared to act in a prehospital emergency, where anything beyond BLS is required [6][7][8][9][10][11][12][13]. Therefore Sheffield medical students approached the local mountain rescue team (Edale), requesting an elective attachment to learn prehospital care skills.…”
Section: Introductionmentioning
confidence: 99%
“…[18] The graduates, therefore, appreciated having been 'allowed to assist with emergencies' as students (GS1), but wished they could have had more exposure (GW5b). [19] Lecturers would enjoy having case discussions in smaller groups (EC5) and suggested that students get 'exposed to prehospital emergency care' (EC13b) [20,21] and are 'assign[ed] specific roles Allowing students to 'assist with emergencies' and not to ask them to wait outside, and practical experience in managing emergencies (simulation and hospital) [35] Experiential clinical learning GS2 'Repetition of basic skills' from third year onwards; start early in third year [34] Skills and short courses/health professions educational practice GS3…”
Section: Experiential Clinical Learningmentioning
confidence: 99%
“…Getting a chance to work with 'equipment you had never worked with' before, e.g. defibrillator [20] Skills and short courses GS4 Relaxed, 'low pressure simulation' setting for practising [19] Health professions educational practice GS5 Did 'BLS certificate in third year' . Learn correct principles [17] Skills and short courses GS6…”
Section: Experiential Clinical Learningmentioning
confidence: 99%
“…A novel prehospital care programme was introduced in London in 2008 4. However, few programmes exist specifically for medical students providing the opportunity to deliver hands-on care in the prehospital setting.…”
Section: Introductionmentioning
confidence: 99%